2008
DOI: 10.1073/pnas.0710837105
|View full text |Cite
|
Sign up to set email alerts
|

Compression of auditory space during rapid head turns

Abstract: Studies of spatial perception during visual saccades have demonstrated compressions of visual space around the saccade target. Here we psychophysically investigated perception of auditory space during rapid head turns, focusing on the ''perisaccadic'' interval. Using separate perceptual and behavioral response measures we show that spatial compression also occurs for rapid head movements, with the auditory spatial representation compressing by up to 50%. Similar to observations in the visual system, this occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 31 publications
2
38
1
Order By: Relevance
“…A compression of auditory space has been reported just before the initiation of rapid head movements (23). The velocity of head movements in our study was, on average, smaller than in the study by Leung et al (23); nevertheless, it may have caused some compression.…”
Section: Discussioncontrasting
confidence: 55%
“…A compression of auditory space has been reported just before the initiation of rapid head movements (23). The velocity of head movements in our study was, on average, smaller than in the study by Leung et al (23); nevertheless, it may have caused some compression.…”
Section: Discussioncontrasting
confidence: 55%
“…Given that empirical studies have suggested that auditory stimuli presented from in front and behind might be treated in a qualitatively different manner by the human brain (see Kitagawa et al, 2005;Kitagawa & Spence, 2006;Tajadura-Jiménez et al, 2009;Zampini, Torresan, Spence, & Murray, 2007), we thought that this might have been a factor that helped to account for the effectiveness of the close rear auditory warning signals compared with their far frontal counterparts in the previous two experiments (cf. Leung, Alais, & Carlile, 2008). In our final experiment, therefore, the auditory warning signals were always presented from in front of the participants, and all that was now varied was whether they were presented from close or far away, with the vibrotactile warning signals being presented to the middle of the participant's stomach (i.e., again to the front).…”
Section: Methodsmentioning
confidence: 99%
“…A possible explanation for the measured updating errors might be distortion and compression of auditory space or biases due to representational momentum during head turns (Cooper et al 2008;Leung et al 2008;Feinkohl et al 2014). Leung et al (2008) state that for compressive spatial errors of auditory or visual space during head turns to be revealed, high head velocities of at least 200°/s are needed.…”
Section: Inaccuracy In Auditory Spatial Updating During Active Head Rmentioning
confidence: 99%
“…Leung et al (2008) state that for compressive spatial errors of auditory or visual space during head turns to be revealed, high head velocities of at least 200°/s are needed. In our study, maximal head velocities were around 50°/s (see Fig.…”
Section: Inaccuracy In Auditory Spatial Updating During Active Head Rmentioning
confidence: 99%